Compositional and structural analysis of selected chromosomal domains from Saccharomyces cerevisiae. Issue 1 (6th October 2013) - Hamperl, Stephan; Brown, Christopher R.; Garea, Ana Villar; Perez-Fernandez, Jorge; Bruckmann, Astrid; Huber, Katharina; Wittner, Manuel; Babl, Virginia; Stoeckl, Ulrike; Deutzmann, Rainer; Boeger, Hinrich; Tschochner, Herbert; et al.
Abstract: Chromatin is the template for replication and transcription in the eukaryotic nucleus, which needs to be defined in composition and structure before these processes can be fully understood. We report an isolation protocol for the targeted purification of specific genomic regions in their native chromatin context from Saccharomyces cerevisiae . Subdomains of the multicopy ribosomal DNA locus containing transcription units of RNA polymerases I, II or III or an autonomous replication sequence were independently purified in sufficient amounts and purity to analyze protein composition and histone modifications by mass spectrometry. We present and discuss the proteomic data sets obtained for chromatin in different functional states. The native chromatin was further amenable to electron microscopy analysis yielding information about nucleosome occupancy and positioning at the single-molecule level. We also provide evidence that chromatin from virtually every single copy genomic locus of interest can be purified and analyzed by this technique.